2002
DOI: 10.1038/sj.cgt.7700406
|View full text |Cite
|
Sign up to set email alerts
|

A role for MAP kinase in the antitumor activity of a nucleoside analog

Abstract: Nucleoside analogs ( NAs ) have been used extensively in both antitumor and antiviral therapies. Their general mechanism of action has been postulated to result from incorporation into DNA, leading to disruption of DNA synthesis and DNA polymerase inhibition. To further explore the antitumor mechanisms of NAs we have evaluated ganciclovir ( GCV ), an NA antiviral agent, in herpes simplex virus thymidine kinase ( HSV -TK ) gene -modified tumor cells. This system allows specific evaluation of the antitumor effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been shown that GCV treatment of HSV-TK–expressing tumor cells resulted in the activation of MAP kinase (MAPK). 42 Since MAPK activation is essential for the dedifferentiation of Müller glia and RAG expression after mechanical retinal injury, 13 , 14 it is possible that GCV activated MAPK in Müller glia through an unknown pathway, which in turn led to the high expression of RAGs and subsequent prolonged activation. Another possibility is that there are unknown communicating signals between the dedifferentiated Müller glia and the proliferating MGPCs that function to downregulate RAG expression in Müller glia and promote their transition to a preinjury status.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GCV treatment of HSV-TK–expressing tumor cells resulted in the activation of MAP kinase (MAPK). 42 Since MAPK activation is essential for the dedifferentiation of Müller glia and RAG expression after mechanical retinal injury, 13 , 14 it is possible that GCV activated MAPK in Müller glia through an unknown pathway, which in turn led to the high expression of RAGs and subsequent prolonged activation. Another possibility is that there are unknown communicating signals between the dedifferentiated Müller glia and the proliferating MGPCs that function to downregulate RAG expression in Müller glia and promote their transition to a preinjury status.…”
Section: Discussionmentioning
confidence: 99%